The Stone Age of Qatar: new investigations, new finds; interim report (poster) - Scott-Jackson, Julie E.; Scott-Jackson, William; Al Naimi, Faisal Abdulla; Tetlow, Emma; Crassard, Rémy (Proceedings of the Seminar for Arabian Studies, 2014)
This interim report summarizes the results of fieldwork carried out by the PADMAC Unit during 2012/2013 in a previously unexplored area of southern Qatar. The aim of this series of systematic surveys was to find undiscovered lithic surface-scatters/sites and characterize the assemblages. Prior to fieldwork, a detailed desk-based geospatial analysis of the topography, aerial satellite imagery, and geologic mapping were performed to identify areas for on-site investigation. The validity of these data was confirmed by a ground-truthing field exercise in December 2012. Work in this designated area continued during March and June 2013. Lithic surface-scatters/sites were discovered on the hills capped with (knappable) chert that surround and overlook large depressions, which appear to be fluvial in origin and may indeed have been palaeochannels and palaeolakes (geomorphological modelling suggests that this area of Qatar has remained above sea level for at least the past two million years). The initial analysis of the assemblages from the twenty-one lithic surface-scatters/sites discovered to date (June 2013) indicates that one lithic assemblage can be equated to Qatar Neolithic Group B. Of particular importance however, are the other twenty lithic assemblages that certainly predate the Neolithic (technologically and in terms of patination), appear to include two distinct assemblage types, and may represent two relatively contemporary specialized stages of the chaîne opératoire, or indeed two completely different phases of the Palaeolithic. It is envisaged that the next stage of this research will include the collection of sufficient lithics from each scatters to facilitate rigorous techno-typological analysis; further investigation of particular lithosoils that may well incorporate embedded/stratified lithics; geomorphological investigations in the depressions; and the discovery of more lithic surface-scatters/sites with the aim of resolving the long-standing debate on the stone-age history of Qatar.